Internet Of Things Technology For Monitoring Infusion Fluid Contents - Irfan Sarif, Muhammad; Supiyandi; Pratama, M. Khoiri (Cattleya Darmaya Fortuna, 2024)
Patient care requiring IV fluids is an important aspect in the medical field. Accuracy and speed in monitoring IV fluid content are very important to avoid the risk of over-infusion or under-infusion that can endanger patients. However, manual monitoring methods that are still widely used today have limitations in terms of accuracy and response time. This study aims to develop an Internet of Things (IoT)-based system that can monitor IV fluid content in real-time and send notifications to medical personnel if the IV fluid approaches the critical limit. This system is expected to increase efficiency and accuracy in monitoring IV fluids, as well as reduce the risk of human error. This study uses an IoT-based system development method with the main components being a weight sensor to measure IV fluid content and a communication module to send data to a central server. The collected data will be analyzed in real-time using a data processing algorithm to determine the critical level of fluid. Automatic notifications will be sent via a mobile application or alarm system when the IV fluid approaches a predetermined limit. The results of the study show that the developed system is able to monitor IV fluid content with high accuracy and send notifications in real-time. Tests on a number of patients have shown that the system can significantly reduce the incidence of over-infusion and under-infusion, as well as improve the response time of medical personnel to critical situations. The implementation of this technology is expected to be widely applied in hospitals and other healthcare facilities to improve patient safety.